1983
DOI: 10.1007/bf00426374
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopamine agonists, catecholamine depletors, and cholinergic and GABAergic drugs on acute dyskinesias in squirrel monkeys

Abstract: It has been suggested that the neuroleptic-induced acute dyskinetic syndrome in monkeys may be a useful model of extrapyramidal dysfunction. Various drugs that have well-characterized effects on clinical extrapyramidal syndromes and on catecholaminergic, cholinergic, or GABAergic neurotransmission were assessed in dyskinesia-susceptible squirrel monkeys. Catecholamine depletors (alpha-methyl-p-tyrosine, tetrabenazine) induced the syndrome, as do dopamine (DA) receptor antagonists, and d-amphetamine reversed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
1

Year Published

1986
1986
2006
2006

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 35 publications
1
32
1
Order By: Relevance
“…This suggests some involvement of central cholinergic systems. Neuroleptic-induced acute dyst0nia in man and primates can also be controlled by administration of anficholinergic drugs (Meldrum et al 1977;Casey et al 1980;Porsolt and Jalfre 1981), and cholinergic agonists such as arecoline or physostigmine can exaggerate dystonic reactions initiated by neuroleptics in primates (Neale et al 1984;Casey et al 1980), again suggesting a key role for cholinergic systems.…”
mentioning
confidence: 98%
“…This suggests some involvement of central cholinergic systems. Neuroleptic-induced acute dyst0nia in man and primates can also be controlled by administration of anficholinergic drugs (Meldrum et al 1977;Casey et al 1980;Porsolt and Jalfre 1981), and cholinergic agonists such as arecoline or physostigmine can exaggerate dystonic reactions initiated by neuroleptics in primates (Neale et al 1984;Casey et al 1980), again suggesting a key role for cholinergic systems.…”
mentioning
confidence: 98%
“…When MAP is administered, drowsiness and fatigue disappear, resulting in transient elevation of mental and physical activity tional behavior of AMP-administered rats as well as changes in metabolism, neurotransmitter, behavior, diet/ water intake and endocrinology when AMP or MAP is administered. Although there are some studies that have used monkeys to examine behavioral pharmacology [1,12,13] and drug metabolism [2,6,10], there have been few reports on immunological function. In our study, cynomolgus monkeys were given a single injection of MAP, and changes in blood cell count, biochemistry values, serum cortisone level, natural killer (NK) cell activity and the mitogen response of T-lymphocytes were investigated.…”
mentioning
confidence: 99%
“…TD, conversely, is usually maximal when the drug is wearing off (Gardos et al, 1978), and (although this is controversial), sometimes responds well to cholinomimetics (Moore and Bowers, 1980). However, this confusion of the two side effects has led to controversial practices, because many pharmaceutical companies use the propensity of a drug to induce acute dystonic reactions in "primed" monkeys as an indication of whether a new drug will induce extrapyramidal dysfunction (Neale et al, 1984) even though it has never been demonstrated that these acute dystonic reactions are an accurate predictor of TD development. The highly fluctuating (once a week) neuroleptic regimen in primates clearly contributes to the progressive appearance of this syndrome, and it is noteworthy that humans are never persistently maintained on such an extremely fluctuating drug regimen.…”
Section: Primate Studiesmentioning
confidence: 98%